Self-management in patients with diabetic foot ulcer: a concept analysis† - Zhuang Hui-Ren; You Yong-Mei; Liu Qin; Yu Hai-Ping; De Ala Minerva B. (Sciendo, 2024)
This paper presents an analysis of the concept of patient outcomes.